(u+3)*10=60

Simple and best practice solution for (u+3)*10=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (u+3)*10=60 equation:


Simplifying
(u + 3) * 10 = 60

Reorder the terms:
(3 + u) * 10 = 60

Reorder the terms for easier multiplication:
10(3 + u) = 60
(3 * 10 + u * 10) = 60
(30 + 10u) = 60

Solving
30 + 10u = 60

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + 10u = 60 + -30

Combine like terms: 30 + -30 = 0
0 + 10u = 60 + -30
10u = 60 + -30

Combine like terms: 60 + -30 = 30
10u = 30

Divide each side by '10'.
u = 3

Simplifying
u = 3

See similar equations:

| -38=4(u-6)-6u | | -4c+25=5 | | 8+4m=90m-7 | | -x+1=-48 | | (x/2)-3x=-25 | | 12y+37=121 | | 5x-35=-9(x+7) | | -12=-6y+4(y-6) | | Y-792=6 | | 4x+7x+5x=128 | | 3n-14=70 | | 4(w+4)-8w=-24 | | 2k=8+3k | | -2b+-6=-4 | | 8x-x^2=18 | | 4tanx=9 | | -8/9x=-12/18 | | x/20=100 | | 0=x^2-x-10 | | 20=x+15 | | 3b-6a=g | | 10x+3x+7x=180 | | -9w-41=-5(w+5) | | 4u-7=9(u-3) | | d-407=360 | | -3=5y+7 | | 4=2(u+8)-8u | | 1[2x]+10[1.5x]+9[x]=2250 | | -2(x-9)=8x-32 | | 10v-3v=63 | | x-3.39=9.37 | | -10=5+3v |

Equations solver categories